2009
DOI: 10.1074/jbc.m808597200
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2X7 Receptors Mediate ATP-induced Saliva Secretion by the Mouse Submandibular Gland

Abstract: Salivary glands express multiple isoforms of P2X and P2Y nucleotide receptors, but their in vivo physiological roles are unclear. P2 receptor agonists induced salivation in an ex vivo submandibular gland preparation. The nucleotide selectivity sequence of the secretion response was BzATP Ͼ Ͼ ATP > ADP Ͼ Ͼ UTP, and removal of external Ca 2؉ dramatically suppressed the initial ATP-induced fluid secretion (ϳ85%). Together, these results suggested that P2X receptors are the major purinergic receptor subfamily invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 34 publications
5
77
0
3
Order By: Relevance
“…P2X7 receptors would be the main responsible for the ATP response in this tissue. Purinergic receptor agonist-stimulated salivation was suppressed by more than 70 % in submandibular glands from P2X7 null mice [10]. At least one EC 50 is >100 μM ATP for this receptor [8,41], which is consistent with the high ATP Km we measured for microsomal NTPDases.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…P2X7 receptors would be the main responsible for the ATP response in this tissue. Purinergic receptor agonist-stimulated salivation was suppressed by more than 70 % in submandibular glands from P2X7 null mice [10]. At least one EC 50 is >100 μM ATP for this receptor [8,41], which is consistent with the high ATP Km we measured for microsomal NTPDases.…”
Section: Discussionsupporting
confidence: 87%
“…In submandibular gland (SMG), metabotropic (P2Y 1 , P2Y 2 ) and ionotropic (P2X4, P2X7) receptor subtypes were found, both in basolateral and luminal membranes in acinar and ductal cells [6][7][8]. It was demonstrated that P2X7 activation regulates ionic currents and saliva volume and also induces reactive oxygen species production and inflammatory responses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…On peut conclure de ces résultats que l'ATP libéré en réponse à une stimulation muscarinique régule les sécrétions exocrines via des récepteurs de type P2X 7 [19]. T Nakamoto et al [20] ont mesuré la sécrétion des glandes sous-maxillaires pendant une stimulation de 10 min avec du carbachol. En accord avec les résultats antérieurs obtenus sur la salive totale [15], ils n'ont pas observé de différence dans le volume de salive sécrétée par les glandes sous-maxillaires chez les deux types de souris en réponse à un agent muscarinique.…”
Section: Les Récepteurs Purinergiquesunclassified
“…Il semble donc que ce soit au cours de la phase de sécrétion soutenue (au-delà de 30 min après la stimulation par un agent muscarinique) que l'absence de récepteurs P2X 7 joue un rôle important sur le volume salivaire sécrété [19]. En revanche, T. Nakamoto et al [20] ont montré que l'activation directe des récepteurs P2X 7 stimule la sécrétion sous-maxillaire. Cette sécrétion, en réponse à l'ATP et au benzoyl-ATP (Bz-ATP, un agoniste puissant des récepteurs P2X 7 ), nécessite la présence de calcium dans le milieu de perfusion et est fortement réduite (70 %) chez les souris réunis par une grande boucle extra cellulaire contenant cinq ponts disulfures et des sites de N-glycosylation.…”
Section: Les Récepteurs Purinergiquesunclassified
See 1 more Smart Citation